2013
DOI: 10.1093/schbul/sbs196
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Antipsychotics Cause a Rapid Switch to Fat Oxidation That Is Required for Survival in C57BL/6J Mice

Abstract: Some second-generation antipsychotics (SGAs) increase insulin resistance and fat oxidation, but counter intuitively they do not activate lipolysis. This seems unsustainable for meeting energy demands. Here, we measured dose-dependent effects of SGAs on rates of oxygen consumption (VO 2 ), respiratory exchange ratio (RER), and physical activity in C57BL/6J mice. The role of H1-histamine receptors and consequences of blocking fat oxidation were also examined. Olanzapine, risperidone, and clozapine (2.5-10 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…OLZ is reported to increase reliance on fat oxidation (reduces RER), which can lead to plasma glucose accumulation (Klingerman et al, 2014;Klingerman et al, 2015). This has been thought to be due to central effects of OLZ (Klingerman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OLZ is reported to increase reliance on fat oxidation (reduces RER), which can lead to plasma glucose accumulation (Klingerman et al, 2014;Klingerman et al, 2015). This has been thought to be due to central effects of OLZ (Klingerman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The final version may differ from this version. One of the side effects of OLZ that is thought to perhaps contribute to increased blood glucose is up-regulated fat oxidation (Klingerman et al, 2014). To assess this and to determine whether AICAR can alter or improve these and other metabolic parameters such as activity and heat production, mice were housed in CLAMS metabolic cages and were given one of the four drug treatments.…”
Section: Olz Reduces Rer Oxygen Consumption Activity Levels and Heamentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, decreased level of physical activity could be partially due to the sedative effects of the drugs. [ 44 ] A prolonged decrease in physical activity without reduction of food intake causes the accumulation of adipose tissue,[ 45 ] which was mentioned above as a potential cause of insulin resistance. Hence, the combination of metabolic adverse effects and inactivity can lead to obesity, while obesity and inactivity can adversely affect the metabolic parameters as well.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that schizophrenic patients suffer from cardiometabolic disorders (Jones et al, 2013;Pasternak et al, 2014;Wang et al, 2014), and administration of antipsychotic drugs is followed by higher morbidity and mortality (Jones et al, 2013). Several adverse effects, particularly prolonged QT intervals, higher rates of arrhythmias (Dineen et al, 2003;Drici et al, 1998;Gurovich et al, 2003), elevated risk of hyperlipidemia (Dudek et al, 2016;Horska et al, 2016;Takeuchi et al, 2015), increased blood glucose and lower circulating levels of free fatty acids (Albaugh et al, 2012;Klingerman et al, 2014) have been reported after olanzapine administration. Despite the fact that the incidence of sudden cardiac or sudden unexpected death in olanzapine-treated patients is twice as high as in nonusers (Salvo et al, 2016), the mechanism underlying the severe, adverse cardiac effects remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%